Tinjauan Fiqh Muamalah terhadap Bai’atain fi Bai’ahpada Jual Beli Kain di Karangnunggal Kabupaten Tasikmalaya - Deliya Fadilatul Ihsani; Iwan Permana; Zia Firdaus Nuzula (UNISBA Press, 2023)
Abstract. Bai'atian fi bai'ah is a form of sale and purchase transaction system in which there are restrictions based on unclear which contract is used in a sale and purchase transaction. Buying and selling transactions with bai'atain fi bai'ah itself has various community responses, both those who agree and disagree with the implementation of such a buying and selling system, especially in the fabric world in Karangnunggal, Tasikmalaya Regency. The purpose of this study was to examine the suitability and legal validity of bai'atain fi bai'ah, especially in the aspect of fiqh mua'malah, this research was conducted using qualitative research methods with descriptive methods, the result of this study is the concept of bai'atain fi bai The law that is applied and carried out in Karangnunggal Tasikmalaya is running with adjustments to the acceptance of each party in the transaction without the need to make a thorough agreement in the area which causes many differences in the application of the cloth buying and selling system in Karangnunggal, Tasikmalaya Regency, apart from that the buying and selling transactions carried out in Karangnunggal, Tasikmalaya Regency, was carried out on the grounds that no party felt disadvantaged when using such a trading system, they even felt that they benefited from such a trading system. And based on the fiqh mua'amalah review, buying and selling transactions with the bai'atain fi bai'ah system were sentenced to be prohibited because of religious texts because in its implementation there are elements or 'illat which harm such as gharar. However, not a few express their agreement with the application of this system on condition that there is an agreement agreed upon by the parties to the transaction and it is considered that the transaction is valid and does not deviate from religious law. scholars are considered not to meet the requirements of buying and selling and there is an 'illat which makes transactions with this system prohibited. Abstrak. Bai’atian fi bai’ah merupakan suatu bentuk sistem transaksi jual beli yang terdapat pelarangan berdasarkan ketidakjelasan pada akad mana yang digunakan dalam suatu transaksi jual beli tersebut. Transaksi jual beli dengan bai’atain fi bai’ah sendiri memiliki berbagai penanggapan masyarakat baik itu yang setuju dan tidak setuju atas penerapan sistem jual beli seperti itu khusus nya didunia kain di Karangnunggal Kabupaten Tasikmalaya. Tujuan dari penelitian ini adalah untuk meneliti mengenai kesesuaian serta keabsahan hukum dari bai’atain fi bai’ah terutama pada aspek fiqh mua’malah, penelitian ini dilakukan menggunakan metode penelitian kualitatif dengan metode deskriptif, hasil dari penelitian ini ialah konsep bai’atain fi bai’ah yang diterapkan serta dilakukan di Karangnunggal Tasikmalaya ini berjalan dengan penyesuaian terhadap penerimaan setiap pihak yang bertransaksi tanpa perlu membuat kesepakatan secara menyeluruh didaerah tersebut yang menyebabkan banyak nya perbedaan penerapan sistem jual beli kain di Karangnunggal Kabupaten Tasikmalaya selain hal tersebut transaksi jual beli yang dilaksanakan di Karangnunggal Kabupaten Tasikmalaya tersebut dilakukan dengan alasan tidak ada pihak yang merasa dirugikan ketika menggunakan sistem jual beli seperti itu bahkan mereka merasa diuntungkan dengan sistem jual beli seperti itu. Dan berdasarkan tinjauan fiqh mua’amalah transaksi jual beli dengan sistem bai’atain fi bai’ah dijatuhi hukum dilarang karena nash agama sebab dalam pelaksanaan nya terdapat unsur atau ‘illat yang memadharatkan seperti gharar. akan tetapi tak sedikit yang menyatakan kesetujuan akan penerapan sistem ini dengan syarat terdapatnya kesepakatan yang disepakati oleh para pihak yang bertransaksi dan dianggap transaksi tersebut sah dan tidak menyimpang dari syariat agama